Sistem Informasi Penyewaan Lapangan Futsal Pada Rafhely Futsal By Pass Berbasis Web - Buana, Wira; Suherman, Yanni; Azandra, Erien Nada; Sari, Mike Febri Mayang; Hariyandi, Andriyas (Brahmana : Jurnal Penerapan Kecerdasan Buatan, 2023)
This research was conducted at the Rafhely Futsal Bypass, especially in the administration section, which aims to simplify the scheduling process so that it is optimal, make it easier for customers in the field rental process, make it easier for customers to make field payments. This research uses field research methods, library research, while the development method in this research is made using the waterfall method, which provides a general picture of the requirements for the software that you want to make so that it can be seen in detail in terms of what the input, process or output are like. The process and stages of waterfall and system development, it is hoped that after identifying user needs, the software created can be accepted by users. The information system designed is web-based, using the PHP programming language with Codeigniter 4 and MySQL database. This research produces a futsal field rental information system so that this data management system can help the administration process rental data, make it easier for customers to make payments, and present reports to management that are processed systematically, quickly, accurately, up to date, and practically to avoid errors in data management, so that problems with the Rafhely Futsal Bypass can be resolved.